Structural investigation of SiSn/(reduced graphene oxide) nanocomposite powder for Li-ion battery anode applications - Masahiro Kawasaki (2018)
© 2016 Author(s). We synthesized SiSn/(reduced graphene oxide (rGO)) nanocomposite powder for a Li-ion battery material and characterized the structure by transmission electron microscopy (TEM) and analytical scanning transmission electron microscopy (STEM). Graphene oxide was prepared by Hummers method. The graphene oxide powder processed by heat treatment was added together with Si powder into a solution of SnCl2· 2(H2O) dissolved in N2bubbled ethylene glycol, and the solution was reacted with NaBH4. The product had a nominal atomic ratio of Si: Sn: C = 14: 3.5: 100. High-resolution TEM/STEM analysis revealed that the powder consisted of crystalline particles of Sn, Si, and SiO as well as thin reduced graphene oxide (rGO) lamellae of amorphous-like graphite with distorted lattices that were often found in areas as local as a few nm2. The aggregated Si and SiO particles grew up to several hundred nm across. Sn particles grew as large as a few tens of nm while those as small as a few nm were scattered on the (0001) rGO surface with some epitaxial relations. Si, SiO, and Sn particles were found hanging on at the edges of the rGO lamellae. An electrochemical test was performed for this nanocomposite powder. The result suggested that the SiSn/rGO powder would be a promising anode material for lithium-ion batteries with high capacity.